Zinc finger proteins: guardians of genome stability - Kamaliyan, Zeeba; Clarke, Thomas L. (Frontiers in Cell and Developmental Biology, 2024)
Zinc finger proteins (ZNF), a unique yet diverse group of proteins, play pivotal roles in fundamental cellular mechanisms including transcription regulation, chromatin remodeling, protein/RNA homeostasis, and DNA repair. Consequently, the mis regulation of ZNF proteins can result in a variety of human diseases, ranging from neurodevelopmental disorders to several cancers. Considering the promising results of DNA damage repair (DDR) inhibition in the clinic, as a therapeutic strategy for patients with homologous recombination (HR) deficiency, identifying other potential targetable DDR proteins as emerged vulnerabilities in resistant tumor cells is essential, especially when considering the burden of acquired drug resistance. Importantly, there are a growing number of studies identifying new ZNFs and revealing their significance in several DDR pathways, highlighting their great potential as new targets for DDR-inhibition therapy. Although, there are still many uncharacterized ZNF-containing proteins with unknown biological function. In this review, we highlight the major classes and observed biological functions of ZNF proteins in mammalian cells. We briefly introduce well-known and newly discovered ZNFs and describe their molecular roles and contributions to human health and disease, especially cancer. Finally, we discuss the significance of ZNFs in DNA repair mechanisms, their potential in cancer therapy and advances in exploiting ZNF proteins as future therapeutic targets for human disease.